Increased Thermal Challenges Differentially Modulate Neural Plasticity and Stress Responses in Post-Smolt Atlantic Salmon (Salmo salar) - Tang, P. A.; Gharbi, N.; Nilsen, T. O.; Gorissen, M.; Stefansson, S. O.; Ebbesson, L. O. E. (Frontiers in Marine Science, 2022)
The transfer success of farmed post-smolt Atlantic salmon (Salmo salar) depends on proper stress responses and cognitive functions during the early seawater (SW) phase. However, with increasing summer oceanic temperatures, these processes may become challenged implicating allostasis and welfare. Therefore, we examined the effect of post-smolt transfer from 10ºC SW to elevated temperatures (13ºC, 16ºC, and 18ºC) on plasma cortisol and telencephalic genes modulating cognition (neurod, bdnf, pcna, c-fos) and stress-axis regulation (crf, crfbp, mr, gr1, gr2 and hsd11b2). Fish were sampled at i) 1-day following transfer, ii) 45-days of acclimation, and iii) 45-days, 1h after an acute challenge test (ACT) using confinement stress. Fish transferred to 13ºC retained stress responses, elevating cortisol, crf, mr, gr2, c-fos, bdnf levels and maintaining levels of neurod and pcna. Contrastingly, although cortisol increased at 16ºC, telencephalic genes reverted to an inhibition of stress responses, increasing crfbp and gr1 complemented with dampened bdnf, neurod and c-fos responses. However, transferring post-smolts to 18ºC showed the most adverse effects, having absent stress responses (cortisol and c-fos), elevated crfbp and a suppression of hsd11b2 and neurod. The hsd11b2 downregulation implies low cortisol inhibition aligning to absent modulations in corticosteroid receptors and stress responses. These results suggest transfer to 16ºC and 18ºC inhibit the normal reactive response of post-smolts. Following acclimation (45-days), cortisol levels were basal for all groups, however, post-smolts at 16ºC and 18ºC maintained a telencephalic inhibition of key regulatory genes (crf, mr, gr2 and hsd11b2), alongside a lower mr/gr1 ratio, an indicator of chronic allostatic load. Moreover, neural plasticity (neurod and pcna) was suppressed at 16ºC and 18ºC, suggesting impacts of elevated allostatic loads with potentially inferior cognitive capacities. Despite maintaining similar plasma cortisol responses to ACTs, post-smolts at 16ºC and 18ºC elevated neural activation (c-fos) to stress, implying greater challenges, with the 18ºC group also elevating bdnf. In summary, the telencephalon shows that post-smolts transferred to 16ºC and 18ºC continue to struggle with the thermal allostatic loads even after acclimation, which is not revealed by plasma cortisol levels, grounding the importance of telencephalic measures in identifying environmental thresholds and hidden challenges.